Comprensión lectora y logros de aprendizaje en el área de ciencias sociales en estudiantes del nivel Secundaria del Crfa Santa Teresa I Zona, Distrito de Yavarí 2023 - Maricahua Shuña, Ruth Elena (2024)
Unraveling the connection between text comprehension and achievements in Social Sciences of the students of the CRFA Santa Teresa I Zone, Yavarí, during 2023, was the goal of the study, of a sample segment of 95 students selected from a population of 104, a reading evaluation was implemented along with the analysis of academic records. 85.3% of those with high understanding achieved the expected results, while 14.7% with a medium level remained in process. These findings highlight the relevance of strengthening reading skills, promoting educational success. Spearman's coefficient (r=0.752, r=0.730, r=0.702) corroborated the strong correlation between reading and learning.